Diagnostic Lymphocytosis as a Favorable Prognostic Factor in Childhood Acute Myeloblastic Leukemia - Ardianto, Bambang; Christine, Christine; Armytasari, Inggar; Triasih, Rina; Supriyadi, Eddy; Sutaryo, Sutaryo (Asian Pacific Journal of Cancer Nursing, 2025)
Objective: Childhood acute myeloblastic leukemia (AML) has been associated with an unfavorable prognosis, particularly in lower-middle-income countries (LMICs). The limited resources for cytogenetic-based risk stratification in many LMICs constitute the contributing factors. To improve the outcomes of childhood AML, a better understanding of its pathogenesis, which further leads to the development of applicable risk stratification criteria, is required. Studies on adult AML linked lymphocytosis due to increased regulatory T-cells (Tregs) in the bone marrow stroma with a higher risk of remission failure and an early relapse. Since Treg population is influenced by age-dependent bacterial colonization, conducting a study on children with AML is reasonable. Methods: A retrospective cohort study involved 60 patients younger than 18 years with non-M3 AML, 25 of whom had diagnostic absolute lymphocyte counts (ALC0) of less than 4.7 x 109 cells/L and 35 of whom had ALC0 of more than 4.7 x 109 cells/L. These patients were observed for the occurrence of events, which consisted of remission failure, relapse, and death, within five years of treatment. Results: Patients with ALC0 of more than 4.7 x 109 cells/L had the higher five-year event-free (EFS, 24% vs. 0%; p = 0.01) and overall survivals (OS, 31% vs. 10%; p = 0.02). Cox regression analysis demonstrated that ALC0 of less than 4.7 x 109 cells/L was an independent prognostic factor for the lower five-year EFS (hazard ratio [HR], 3.5; 95% confidence interval [95% CI], 1.7 – 7.5; p < 0.01) and OS (HR, 2.1; 95% CI, 1.1 – 4.0; p = 0.03). Conclusion: In contrast to studies in adults, our study showed a correlation between diagnostic lymphocytosis and higher five-year EFS and OS.